Non-Transcriptional and Translational Function of Canonical NF-κB Signaling in Activating ERK1/2 in IL-1β-Induced COX-2 Expression in Synovial Fibroblasts - Nakano, Rei; Kitanaka, Taku; Namba, Shinichi; Kitanaka, Nanako; Suwabe, Yoko; Konno, Tadayoshi; Yamazaki, Jun; Nakayama, Tomohiro; Sugiya, Hiroshi (Frontiers in Immunology, 2020)
The pro-inflammatory cytokine interleukin 1β (IL-1β) induces the synthesis of prostaglandin E2 by upregulating cyclooxygenase-2 (COX-2) in the synovial tissue of individuals with autoimmune diseases, such as rheumatoid arthritis (RA). IL-1β-mediated stimulation of NF-κB and MAPK signaling is important for the pathogenesis of RA; however, crosstalk(s) between NF-κB and MAPK signaling remains to be understood. In this study, we established a model for IL-1β-induced synovitis and investigated the role of NF-κB and MAPK signaling in synovitis. We observed an increase in the mRNA and protein levels of COX-2 and prostaglandin E2 release in cells treated with IL-1β. NF-κB and ERK1/2 inhibitors significantly reduced IL-1β-induced COX-2 expression. IL-1β induced the phosphorylation of canonical NF-κB complex (p65 and p105) and degradation of IκBα. IL-1β also induced ERK1/2 phosphorylation but did not affect the phosphorylation levels of p38 MAPK and JNK. IL-1β failed to induce COX-2 expression in cells transfected with siRNA for p65, p105, ERK1, or ERK2. Notably, NF-κB inhibitors reduced IL-1β-induced ERK1/2 phosphorylation; however, the ERK1/2 inhibitor had no effect on the phosphorylation of the canonical NF-κB complex. Although transcription and translation inhibitors had no effect on IL-1β-induced ERK1/2 phosphorylation, the silencing of canonical NF-κB complex in siRNA-transfected fibroblasts prevented IL-1β-induced phosphorylation of ERK1/2. Taken together, our data indicate the importance of the non-transcriptional/translational activity of canonical NF-κB in the activation of ERK1/2 signaling involved in the IL-1β-induced development of autoimmune diseases affecting the synovial tissue, such as RA.